CONSUMER CURRENT TRENDS IN RESTAURANT INDUSTRIES: A CASE STUDY OF FOOD BLOGGER - Mbouw, Esa; Qonita, Khansa (Emerging Markets : Business and Management Studies Journal, 2018)
The trend of food and beverage industry in Indonesia has shown a great transformation with a help from the current existing technologies. A food related blog is one the trend these days, especially for the millennial. Perceived Usefulness (PU) is one of the factor suggested by researches towards adaptation of technology. However, the perceived usefulness (PU) of a food blogger itself is still questioned on whether the millennial has the intention to follow the food blogger ?s recommendation to choose restaurants. Therefore, the purpose of this study is to determine whether there is a significant relationship between food blogger perceived usefulness and behavioral intention to follow its recommendation. The questionnaire was distributed to 100 food blog readers who have read any food related blog before. The data was processed by using SPSS to obtained the result of this study. The result has shown that food blogger influences the consumer behavioral intention of the readers to follow its recommendation of the food blogger.